From stem cells to neurons and glia: a soxist's view of neural development. - Wegner, Michael; Stolt, Claus (Trends in Neurosciences, 2005)
During nervous system development, neural stem cells give rise to many different types of neurons and glia over an extended period. Little is known about the intrinsic factors that regulate stem-cell maintenance, decide whether neurons or glia are generated, or control terminal differentiation. Transcription factors of the Sox family provide important clues about the control of these events. In the central nervous system (CNS), Sox1, Sox2 and Sox3 are required for stem-cell maintenance, and their effects are counteracted by Sox21. Sox9, by contrast, alters the potential of stem cells from neurogenic to gliogenic, whereas Sox10 is essential for terminal oligodendrocyte differentiation. In the peripheral nervous system (PNS) the same Sox proteins have different functions, uncovering important developmental differences between the CNS and PNS. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.fromst